Low cement structural lightweight concrete with optimized multiple waste mix design - Sampaio, Zodinio Laurisa Monteiro (2017)
The high-energy demand involved in the construction industry and the increasing consumption of concrete made this material an ideal option for the recycling of by-products from various industries such as: porcelain polishing residue (PPR); tire rubber residue (TRR) and limestone residue (LSR). These residues often lack a treatment that contributes to the degradation of the environment. In this sense, the use of by-products that increases the volume of the concrete without damaging significantly its properties, can be a viable option in the production of low-cost and sustainable low-weight concrete (LWC). The main objective of this work was to analyze the mechanical and thermal behavior of structural lightweight concrete (SLWC) with low cement consumption, produced with expanded clay (EC) in replacement of the aggregate and with the addition of PPR, TRR and LSR to replace the small aggregate. For this purpose, a 2³ factorial design was used for the choice of SLWC with the best performance in terms of consistency, mechanical properties and density. Subsequently, reductions of 10, 20 and 30% of cement were performed on SLWC that presented better combination of properties and waste consumption and were characterized by mechanical tests. The best SLWC mix resulting from the combination of mechanical properties and cement consumption was characterized by permeability, flexural strength, TG/DTA, XRF, SEM, thermal capacity, thermal conductivity and thermal diffusivity. The results showed that residues contents around 21% presented better combination of properties. By maintaining the amount of residue at optimum levels it was possible to produce a SLWC with good rheological, mechanical and thermal properties with minimum cement consumption.